Recovery of Polyols from Polyurethane Foam Wastes by Solvent Decomposition. Issue 4 (August 2019) - Li, Qi; Xu, Weitao; Xi, Enhua; Pang, Yanfang; Liu, Xiaosheng; Mao, An
Abstract: The objective of this study was to investigate the feasibility of recovering the polyols from the polyurethane (PU) foam wastes obtained from automobile shredder residue (ASR) by chemical decomposition using the diethylene glycol (DEG) as the decomposing solvent and sodium hydroxide (NaOH) as the catalyst, respectively. The effects of temperature (180 °C and 210 °C), time (0.5, 1, 1.5, 2, 2.5, and 3 hours), and DEG/FPU weight ratio (2:1, 3:1, and 4:1) on the decomposition reaction and the properties of the recovered polyols were investigated. Higher temperature and DEG/FPU weight ratio promoted the FPU decomposition reaction and resulted in lower viscosity, higher hydroxyl number, and higher amine number of the recovered polyols. The hydroxyl number and amine number increased as the reaction progressed, while the viscosity decreased. Once the reaction was completed, little change was observed for the hydroxyl number and viscosity of the recovered polyols. The recovered polyol obtained at 210 °C and DEG/FPU weight ratio of 3:1 showed about the same length of time for the reaction, as well as the physical properties to that obtained at 180 °C and DEG/FPU weight ratio of 4:1.